2014
DOI: 10.1302/0301-620x.96b1.32117
|View full text |Cite
|
Sign up to set email alerts
|

Progression of spinal deformity in wheelchair-dependent patients with Duchenne muscular dystrophy who are not treated with steroids

Abstract: We determined the frequency, rate and extent of development of scoliosis (coronal plane deformity) in wheelchair-dependent patients with Duchenne muscular dystrophy (DMD) who were not receiving steroid treatment. We also assessed kyphosis and lordosis (sagittal plane deformity). The extent of scoliosis was assessed on sitting anteroposterior (AP) spinal radiographs in 88 consecutive non-ambulatory patients with DMD. Radiographs were studied from the time the patients became wheelchair-dependent until the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…The current life expectancy of≥30 years [16, 17] and a mean “late-ambulatory II” age of 19 years from our data indicate patients spend >10 years with impaired hand function, emphasising the importance of preventive and therapeutic measures to maintain hand function [14, 18]. Sitting ability facilitates mobility, social participation, eating, and eye-level communication, but becomes impaired by scoliosis, a frequent complication in non-ambulatory DMD patients [19, 20]. Standards recommend regular monitoring and surgical correction for scoliosis in non-ambulatory patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…The current life expectancy of≥30 years [16, 17] and a mean “late-ambulatory II” age of 19 years from our data indicate patients spend >10 years with impaired hand function, emphasising the importance of preventive and therapeutic measures to maintain hand function [14, 18]. Sitting ability facilitates mobility, social participation, eating, and eye-level communication, but becomes impaired by scoliosis, a frequent complication in non-ambulatory DMD patients [19, 20]. Standards recommend regular monitoring and surgical correction for scoliosis in non-ambulatory patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…In those at high risk of a rapid deterioration, it is suggested that surgery should be performed once the curve progresses beyond 20° (34). In some patients, surgery may not be required if at skeletal maturity, the rate of scoliosis progression plateaus (24).…”
Section: Timing Of Surgerymentioning
confidence: 99%
“…(5) More commonly, changes in bone health result in the development of kyphosis and scoliosis that compromise posture, often resulting in a cascade of vertebral fractures and exacerbation of respiration difficulties in DMD patients. (6) Poor bone health is thought to result partly from a lack of proper mechanical loading on bone, (3) as well as chronic inflammation in dystrophic muscle that can stimulate osteoclastogenesis and bone resorption (4) and may also contribute to delayed bone fracture healing. (7) There is also persistent vitamin D insufficiency in most DMD patients (8) that may affect bone health.…”
Section: Introductionmentioning
confidence: 99%